2022-RA-825-ESGO The impact of age on prognosis in women with endometrial cancer: a pooled analysis of the PORTEC-1, -2 and -3 randomised trials. (20th October 2022) - Wakkerman, Famke Charlotte; De Boer, Stephanie M; Powell, Melanie E; Leary, Alexandra; Fyles, Anthony; Mileshkin, Linda R; Singh, Naveena; Nout, Remi A; Jürgenliemk-Schulz, Ina M; Jobsen, Jan J; Lutgens, Ludy CHW; van der Steen-Banasik, Elsbieta M; et al.
Abstract : Introduction/Background: Numerous studies showed that elderly women with endometrial cancer (EC) have a higher risk of recurrence and cancer-related death. It is unclear whether ageing is a risk factor by itself, or whether other risk factors become increasingly common at older age. We addressed to this using the large PORTEC collection of molecularly classified EC with long-term follow-up data. Methodology: Data of 1801 women participating in the randomised PORTEC trials were pooled and analysed. PORTEC-1 included 714 women with intermediate-risk EC, PORTEC-2 427 with high-intermediate risk EC, and PORTEC-3 660 with high-risk EC. Overall recurrence-free and EC-specific survival were estimated using Kaplan-Meier's method. Prognostic value of age (continuous) was determined by multivariable Cox regression analyses with correction for all significant risk factors identified by univariable analyses. Results: Median follow-up was 12.3 years for PORTEC-1, 10.5 years for PORTEC-2 and 6.1 years for PORTEC-3. Overall recurrence-free and EC-specific survival significantly decreased with age ( figure 1 ). The relation of age with clinicopathological and molecular variables of EC is shown in table 1 . Women ≥60 years had significantly less often POLE mut (5.7% vs. 18.2%) and more often p53abn EC (16.1% vs. 7.6%, p<0.0001). In multivariable analysis, age was an independent risk factor for overall recurrence with a hazard ratio (HR) of 1.03 per year (95%CI 1.02–1.05; p<0.0001), corrected for stage, histotype and grade, myometrial invasion, lymphovascular space invasion (LVSI), molecular class and received adjuvant treatment. Likewise, age had independent prognostic value for EC-specific survival with an HR of 1.05 per year (95%CI 1.02–1.07; p<0.0001), corrected for stage, histotype and grade, LVSI and molecular class. Conclusion: The molecular profile of elderly women was less favourable. The risk of recurrence and EC-related death continuously increases with age, especially from 60 years onwards. Our study showed that age is a significant and independent prognostic risk factor.